Introduction to intelligent biocomposite materials - Muhammad Khusairy, Bakri; Md. Rezaur, Rahman; Murtala, Namakka (Woodhead Publishing, 2026)
Intelligent biocomposite materials are developing at the convergence of modern manufacturing and artificial intelligence (AI), through research and the use of natural materials. Natural fibers and renewable bio-based matrices offer a sustainable alternative to traditional undecomposed composites, which exhibit properties such as self-healing, stimulus responsiveness, and environmental adaptation. Therefore, in this chapter, the biocomposite structure, its properties, composition, and correlations were analyzed, including the incorporation of intelligent features that broaden their use across several sectors. Biocomposite development has facilitated its use in various industries, including transportation, building, healthcare, and intelligent packaging. Intelligent biocomposite behavior adapts to temperature, humidity, and stress, improving durability and performance, while self-healing biocomposites address maintenance, environmental, and durability issues. Despite these advances, intelligent biocomposites have challenges in manufacturing scalability, material consistency, and functional quality improvement. The evolving field of AI in biocomposite systems is capable of enhancing material design, enabling real-time monitoring and predicting performance. Therefore this chapter will identify the potential areas and find the critical research gaps for investigation. The crucial materials' green technologies and their importance may enable the global transition to sustainable and intelligent material systems. Lastly, this comprehensive resource chapter aims to provide scholars and industry professionals involved in the next generation of biocomposites by combining existing research, case studies, and new technologies.